Comparison of Round Window Anatomy between Pediatric and Adult Population: A Perspective from Cochlear Implantation Surgery - Pradhananga, Rabindra B; Gyawali, Bigyan R; Rayamajhi, Pabina (Journal of Institute of Medicine Nepal, 2020)
Introduction The round window is thought to be an ideal port for inserting electrodes during cochlear implantation. Considering its complex anatomy with an individual variation, this study aims to review the anatomy of round window based on the visibility of round window niche and round window membrane via posterior tympanotomy in pediatric and adult population who underwent cochlear implantation.MethodsThis was a retrospective observational study conducted at the Department of ENT-HNS, Institute of Medicine, Kathmandu, Nepal. Surgical notes of adult (>15 years) and pediatric cases (